Urban Renewal Project Selection Using the Integration of AHP and PROMETHEE Approaches - Polat, Gul; Damci, Atilla; Gurgun, Asli Pelin; Demirli, Ilayda (ELSEVIER SCIENCE BV, 2016)
Appropriate project selection has a significant impact on construction companies' success. Selecting the appropriate project is complicated due to uncertainties related to many factors that may influence the project selection process. The uncertainties related to a construction project may vary according to the type of the construction project. Therefore, having a project selection tool, which assists construction companies in selecting a particular construction project, can be a significant advantage in achieving success. Urban renewal projects constitute a significant portion of the projects that are carried out by construction companies in Turkey. This study aims to propose an integrated approach for selection of urban renewal projects. The proposed approach combines analytic hierarchy process (AHP) method and PROMETHEE, to help construction companies in selecting the appropriate urban renewal project. AHP and PROMETHEE were used to find the weights of the selection criteria and to rank the alternative projects, respectively. The proposed approach is used to solve a project selection problem of a Turkish construction company, which is mainly specialized in urban renewal projects. In the case study, twelve different projects were ranked according to seventeen evaluation criteria by using the proposed approach. The findings of this study revealed that the proposed approach can be a useful tool for construction companies, which are especially specialized on urban renewal projects. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: Analytic hierarchy process; case study; project selection; promethee; urban renewal projects; DECISION-MAKING; Construction & Building Technology